Reflections on Mentoring Online Doctoral Learners through the Dissertation. Issue 1 (1st January 2021) - Elmore, Robert L.
Abstract: Writing a dissertation can be a daunting task for any learner. Yet online doctoral learners often face additional challenges. In my experience as an online doctoral dissertation mentor, learners typically face five common challenges: writing, feelings of isolation, access to resources online, establishing a professional and collegial relationship with their mentor, and managing the research component. The primary responsibility of online mentors involves helping their learners navigate these challenges, while often facing challenges of their own, many unique to the online environment. My experience as an online dissertation mentor includes both the role of dissertation mentor and as chair of the dissertation committee. This relationship with the mentee begins at the dissertation stage, after successful completion of all coursework and any written exam that is required for graduation. This article will focus on how a mentor in a fully online doctoral program can help the doctoral learner navigate these five areas of challenge, and what skills the mentor must develop to be effective. Although the role of the mentor and the resources provided by the university may vary, the recommendations included here should be relevant to all online mentors.